Density From Two Populations Of Local Invasive Species Arenga obtusifolia Mart. In Nature Reserve Forest, West Sumatera - Hartika, Meitri; Syamsuardi, Syamsuardi; Nurainas, Nurainas (Metamorfosa: Journal of Biological Sciences, 2019)
Lembah Anai and Rimbo Panti nature reverse forest were conservation area that supppsed getting invacived by Langkap ( Arenga obtusifolia Mart.). Since Langkap has tendency to invaded this conservation area so it is necessary to do a research about species of invasive for density of Langkap in Lembah Anai and Rimbo Panti nature reverse area. The aim this study was to determine of characteristic reproductive, dispersal and density of Langkap  in two populations. Collecting sample was used quadrat method. For the density of A. obtusifolia Mart. in Cagar Alam Rimbo Panti higher than in Cagar Alam. Lembah Anai. This is because the vegetation in Cagar Alam Rimbo Panti slightly so that A. obtusifolia Mart. more dominating the area. Keywords : Invasive species, A. obtusifolia Mart. , C agar A lam Lembah Anai, C agar A lam Rimbo Panti, density .